Metode Penugasan melalui pembelajaran IPS untuk Meningkatkan Hasil Belajar Siswa - Fadhli Dzil ikrom (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
Researchers use the Classroom Action Research (PTK) or Classroom Action Research method to make it easier to prepare research according to the title "Assignment Method through Social Studies learning to Improve Student Learning Outcomes (Classroom Action Research at SDN Panancangan I, Serang City)". Increasing learning outcomes through social studies learning by applying the assignment method, it can be seen that in the pre-cycle the average score in class 5 was 26.6 with completeness being 0%, while in cycle I it rose to 51.2, the class average with completeness being 28%, namely 8 students completed the evaluation of their learning outcomes and continued in cycle II, namely an increase in learning outcomes to 65.3, the class average with a completion percentage of 78% (22 students completed and 6 students did not complete) and in the last cycle there was a significant increase to 78.6 class average, with 100% student completion.               Based on the results of the pre-cycle, cycle I, cycle II, up to cycle III, it can be concluded that through the application of the Assignment Method through social studies learning to improve student learning outcomes (Classroom Action Research at SDN Panancangan I, Serang City) there has been a graphic increase in learning outcomes in each the cycle. The statement of the research results can be declared successful or can be said to be significant through the stages of the cycle